2023
DOI: 10.3389/fpara.2023.1113950
|View full text |Cite
|
Sign up to set email alerts
|

Early immune and host cell responses to Cryptosporidium infection

Abstract: Cryptosporidium spp. are opportunistic protozoan parasites that infect epithelial cells of the small intestine and cause diarrheal illness in both immunocompetent and immunodeficient individuals. These infections may be more severe in immunocompromised individuals and young children, especially in children under 2 in developing countries. The parasite has a global distribution and is an important cause of childhood diarrhea where it may result in cognitive impairment and growth deficits. Current therapies are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 158 publications
0
6
0
Order By: Relevance
“…However, these pets are frequent Salmonella carriers, and zoonotic transmission of these bacteria has been extensively reported among owners [ 36 ], with children and immunocompromised hosts at special risk for this infection. In addition, reptiles could be Cryptosporidium carriers [ 6 ], and this pathogen is relevant for immunocompromised hosts [ 37 ]. Many veterinarians are not aware of the zoonotic risk of keeping birds in the household of immunocompromised patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, these pets are frequent Salmonella carriers, and zoonotic transmission of these bacteria has been extensively reported among owners [ 36 ], with children and immunocompromised hosts at special risk for this infection. In addition, reptiles could be Cryptosporidium carriers [ 6 ], and this pathogen is relevant for immunocompromised hosts [ 37 ]. Many veterinarians are not aware of the zoonotic risk of keeping birds in the household of immunocompromised patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our knowledge of cattle chemokine families and their specificity is limited; the ones identified here were not previously reported in dairy cows with respect to C. parvum infection, and also differ from those commonly described in the other species, emphasizing the interspecies differences. As reported in the literature, during cryptosporidium infection, chemokines assist with the migration of inflammatory and adaptive immune cells such as neutrophils, NK cells, macrophages, and DCs to the infection site ( 40 , 41 ). Our bioinformatics analysis suggests the possible recruitment of granulocyte (neutrophils, eosinophils, mast cells and basophils) and mononuclear cell (lymphocytes and monocytes) recruitment during calves’ C. parvum infection, which require further validation.…”
Section: Discussionmentioning
confidence: 99%
“…The other component of adaptive immune cells consists of B cells, whose involvement in the immune response during Cryptosporidium infection is controversial. It has been reported that B cell free mice are able to remove C. parvum parasites, and that Igs do not control protozoan parasite replication ( 41 ). However, it is known that individuals with deficiencies in Igs (IgM and IgA) are more susceptible to Cryptosporidium infection ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The provoked inflammatory response against cryptosporidial infection disturbs the gut homeostasis and results in pro‐inflammatory cytokine release and leukocyte infiltration [63]. Furthermore, dendritic cells produce IL‐12, which helps in macrophage and innate lymphocyte activation, and IFN‐γ generation [64].…”
Section: Discussionmentioning
confidence: 99%